DESIGNING MEASUREMENT OF PH AND WATER TURBIDITY LEVEL BASED ON IOT - Nursobah Nursobah; Asep Nurhuda; Ahmad Fahrijal Pukeng (Jurnal Ilmiah Matrik, 2021)
Research on measuring pH and water turbidity levels based on Internet of Things (IoT) is designed to make it easier for laboratory workers to measure acid and alkaline levels and turbidity levels in water in order to provide fast and efficient service to people who carry out water quality tests. This measuring instrument for pH and water turbidity is based on IoT by utilizing wireless technology in the process of transferring data to a database and using the web as the output media for measuring water content. The system development method used in this research is Prototype. The first stage in this method is to listen to the customer as a form of gathering the needs for the tools to be built, then the second stage is to design and make a prototype that is tailored to the needs of the tools that have been defined previously and the third stage is the prototype trial carried out by the customer by adjusting the request and then providing feedback on the tools developed